2015
DOI: 10.1074/jbc.m115.656785
|View full text |Cite
|
Sign up to set email alerts
|

Deoxyhypusine Modification of Eukaryotic Translation Initiation Factor 5A (eIF5A) Is Essential for Trypanosoma brucei Growth and for Expression of Polyprolyl-containing Proteins

Abstract: Background: eIF5A facilitates translation of mRNAs encoding proteins with polyprolyl repeats. Results: The protozoan parasite Trypanosoma brucei contains polyprolyl tracts in 15% of its proteome, and both eIF5A and its post-translational modification with deoxyhypusine are essential. Conclusion: Loss of eIF5A leads to abnormal cell morphology, abnormal cell division, and decreased flagellar attachment. Significance: Inhibitors of hypusine biosynthesis would disrupt multiple essential cellular processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 50 publications
1
17
0
Order By: Relevance
“…Nevertheless, the degree of activation observed in trypanosome enzyme-prozyme pairs is exceptional. It has been postulated that the dramatic control of enzyme activities via the enzyme-prozyme mechanism was expanded in trypanosomes in response to their lack of transcriptional control and the almost exclusive reliance on posttranscriptional and posttranslational mechanisms of gene regulation (43). The present study is the first report of an enzymeprozyme complex in trypanosomes outside the polyamine synthesis pathway.…”
Section: Discussionmentioning
confidence: 63%
“…Nevertheless, the degree of activation observed in trypanosome enzyme-prozyme pairs is exceptional. It has been postulated that the dramatic control of enzyme activities via the enzyme-prozyme mechanism was expanded in trypanosomes in response to their lack of transcriptional control and the almost exclusive reliance on posttranscriptional and posttranslational mechanisms of gene regulation (43). The present study is the first report of an enzymeprozyme complex in trypanosomes outside the polyamine synthesis pathway.…”
Section: Discussionmentioning
confidence: 63%
“…Gutierrez et al (85) also reported evidence that eIF5A similarly stimulates peptide bond formation at consecutive proline sequences in S. cerevisiae. Additional evidence for the importance of eIF5A in translation of polyproline proteins was reported in T. brucei (86). Recent ribosome profile data demonstrate that eIF5A works more generally at many ribosome-stalled sites and that it also enhances translation termination (87,88).…”
Section: Mode Of Action Of Eif5a In Translationmentioning
confidence: 82%
“…For example, hypusinated eIF5a modulates mitochondrial respiration and macrophage activation via promoting the efficient expression of a subset of mitochondrial proteins involved in the tricarboxylic acid cycle and oxidative phosphorylation (Puleston et al, 2019). eIF5a is also required for efficient translation of mRNAs encoding proteins with poly(Pro) tracts (such as PPP or PPG) by preventing ribosomes from stalling at such sequences (Pereira et al, 2016;Nguyen et al, 2015).…”
Section: Discussionmentioning
confidence: 99%